Addressing Islamic Radicalization in the Digital World: Challenges and Solutions for Generation Z - Najamuddin, Najamuddin; Alifka Alya Zhafirah; Alimin Alwi (International Journal of Education, Vocational and Social Science, 2025)
The radicalization of Islam in the digital world is a major challenge for generation z, especially those who are active in using the internet and social media. This study aims to understand radicalization in the digital world, factors that make the generation vulnerable to radicalization, and the challenges and solutions faced by generation z in preventing radicalization. This study uses a qualitative descriptive approach. Data collection through observation and interviews with generation z who actively use the internet and social media, and analysis of literature from various sources. The results of this study indicate that social media is the main tool in the spread of extreme thoughts carried out by radical groups through digital propaganda, closed discussion forums and the spread of hoax news. Generation z who are in the stage of searching for their identity are vulnerable to being influenced by radical narratives. The main challenges faced are low digital literacy and lack of moderate religious understanding. Meanwhile, solutions that can be done by increasing digital literacy, education that teaches the values of religious moderation, and the active role of families in providing an understanding of tolerant Islam. Generation z is expected to be able to become a driving force that rejects radicalization and supports diversity in this digital era.